2018
DOI: 10.1055/s-0036-1591553
|View full text |Cite
|
Sign up to set email alerts
|

Water-Promoted Chlorination of 2-Mercaptobenzothiazoles

Abstract: Substituted benzothiazoles play an important role in medicinal chemistry due to their pharmacological properties. Their 2-substituted derivatives are often prepared from 2-chlorobenzothiazoles, which in turn can be synthesized from the 2-mercapto precursor using sulfuryl chloride. In practice, this seemingly straightforward and widely used reaction can be impeded by poor reproducibility and low reaction yields. In this communication, we report that the simple addition of water to the reaction leads to remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…13 C{ 1 H} NMR (101 MHz, CDCl 3 ): δ 152.0, 138. 7,136.8,130.6,122.6,115.8,105.3,and 15.7. HRMS (ESI) 341.8669;found,341.8676.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 C{ 1 H} NMR (101 MHz, CDCl 3 ): δ 152.0, 138. 7,136.8,130.6,122.6,115.8,105.3,and 15.7. HRMS (ESI) 341.8669;found,341.8676.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…13 C{ 1 H} NMR (101 MHz, CDCl 3 ): δ 169.2, 152. 7,136.0,127.3,122.9,120.2,119.7,66.2,48.4,. Purified by silica gel column chromatography (eluent: PE/EA = 30:1−10:1).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, this simple procedure gave low yields and was poorly reproducible. In [ 102 ], the authors have found that the simple addition of water substantially increases the effectiveness of the reaction. This effect was assigned to the formation of acid by partial hydrolysis of sulfuryl chloride.…”
Section: 2-mercaptobenzothiazolesmentioning
confidence: 99%
“…The reaction does not depend on the substituents in the reagents. Later on [102], this method was applied to the synthesis of 2-mercaptobenzothiazoles 51d-n (Scheme 43). Their treatment with sulfuryl chloride gave 2-chlorobenzothiazoles 53d-n in excellent yield.…”
Section: Scheme 42 Mercaptobenzothiazoles 50a-c From N-thioacylbenzotriazoles In the Presence Of Pmhsmentioning
confidence: 99%